Double hydrates salt as sustainable thermochemical energy storage materials: Evaluation of dehydration behavior and structural phase transition reversibility. (1st May 2020) - Ait Ousaleh, Hanane; Sair, Said; Zaki, Abdelali; Faik, Abdessamad; Mirena Igartua, Josu; El Bouari, Abdeslam
Highlights: Synthesis and phase transition reversibility of double salts were investigated. Double hydrates salts provided high storage density and good cycling stability. A theoretical approach based on experimental measurements of new TCM was developed. Excellent efficiency of 77.4% and storage density up to 4.7 GJ m -3  were achieved. Abstract: Currently, thermochemical energy storage (TCES) offers the opportunity to relieve the enormous gap of energy demand and supply in the solar energy field. This method has its specific requirements, such as high energy storage density, good thermal stability, high reaction enthalpy, high heat capacity and switched temperature range of thermochemical storage material (TCM) for low to medium temperature building applications. This paper reports the synthesis of blödite-type structure Na2 M(SO4 )2 ·4H2 O (M = Zn, Mg) and copper kröhnkite phase Na2 Cu(SO4 )2 ·2H2 O. Their structural and thermal behavior were also investigated to explore a new temperature range using incorporated salts. An evaluation of potential energy storage density, structural reversibility, thermal cycling stability and storage efficiency of double salts compared to pure hydrates salts as TCM was carried out. The preliminary results show a good structural matching of synthesized double salts confirmed by XRD, FTIR, and Raman spectroscopy, while the transition phase investigation since dehydration process was reported by XRD and Raman spectroscopy. Moreover, Na2 Zn(SO4 )2 ·4H2 O exhibited a suitable charging range temperature (<105 °C), good cycling stability at the first ten hydration/dehydration cycles with an excellent energy storage density of 4.7 GJ m −3 and an interesting theoretical efficiency up to 77.4%.